Verses Rejecting Extremism in the Holy Quran: Selected Examples - An Objective Study (Islamic Sciences Journal, 2025)
ABSTRACTPraise be to Allah, Lord of the Worlds, and peace and blessings be upon the trustworthy Prophet Muhammad, may Allah bless him and grant him peace, who was sent as a mercy to the worlds, and upon his family and all his companions, and upon those who follow their guidance until the Day of Judgment. Now then: This research is entitled: (Verses Rejecting Extremism in the Glorious Qur’an: Selected Examples: An Objective Study). Based on the principles of Islamic law and its goal of achieving social and psychological security, I chose  this topic to clarify the Glorious Qur’an’s position on rejecting extremism, emphasize the strengthening of social security for individuals and groups in the contemporary world, and outline solutions to the contemporary scourge that threatens societal security, namely extremism. I base these solutions on Islamic law.
Keywords: Verses, renunciation, extremism, fanaticism, division.